METHODS OF DEVELOPING ACADEMIC WRITING SKILLS OF STUDENTS (American Journal of Pedagogical and Educational Research, 2023)
Academic writing is a complex phenomenon that includes the creation of both written documents (theses, abstracts, articles) and presentations, oral reports, designed taking into account the requirements of argumentation, the use of a certain metalanguage and discursive markers, as well as other formal features that characterize the scientific style.